PROGRAM ZONPETSI UNTUK MENINGKATKAN MOTIVASI BELAJAR ANAK PADA MASA PANDEMI COVID-19 DI DUSUN MARGAJAYA - Purna Bayu Nugroho (ABDIMAS DEWANTARA, 2022)
This program aims to increase the learning motivation of children in Margajaya Hamlet during the Covid-19 pandemic. The method of implementing this Zonpetsi activity is face-to-face assistance like private lessons and face-to-face learning as in class by showing animated learning videos to children in Margajaya Village. This activity took place from 10 August to 7 September 2020. The result of this activity was an increase in children's learning motivation in Margajaya Hamlet.